Self-incompatibility in pears (Pyrus communis L., Pyrus serotina Rehd. and Pyrus ussuriensis) Review - Halász, J.; Hegedűs, A. (International Journal of Horticultural Science, 2006)
Self-incompatibility system and allele pool of three different pear species, European pear (Pyrus communis), Japanese pear (P. serotina) and Chinese pear (P ussuriensis) are displayed. Several inconsistencies and the absence of the harmonization of three different allele series are revealed in the European pears. By collecting data from several reports eight incompatibility groups of Japanese pear cultivars could be established. A self-compatible genotype is analysed in details and shown to be a stylar-part mutant. As Japanese pear was the first fruit tree species from which S-ribonucleases were identified, the history of S-genotyping from the beginning to the latest achievements and technical developments can be also monitored from the experiments enumerated. In Chinese pears, seven S-alleles and one incompatibility group could be identified.